Special drawing rights : character and use - Gold, Joseph (Washington, 1979)
This pamphlet deals with the amendment of the Articles of Agreement of the International Monetary Fund which has established a facility based on "special drawing rights" that enables the Fund to supplement the existing reserve assets of the monetary authorities of its member states.p1 (BThe amendment was the result of years of intellectual effort and dogged negotiation, and it is an event of great importance. There are complicated reasons why it is important and they cannot be combined into a single apothegm, but one outstanding reason is that the amendment represents a fur ther advance toward the regulation of the international monetary system by law and by the exercise of reason under law.s
Keywords: Financial economics